Front Cover, Volume 40, Issue 11. Issue 11 (22nd October 2019) - Reuser, Arnold J. J.; van der Ploeg, Ans T.; Chien, Yin‐Hsiu; Llerena, Juan; Abbott, Mary‐Alice; Clemens, Paula R.; Kimonis, Virginia E.; Leslie, Nancy; Maruti, Sonia S.; Sanson, Bernd‐Jan; Araujo, Roberto; Periquet, Magali; et al.
Abstract : Front Cover : The cover image is based on the Research Article GAA variants and phenotypes among 1, 079 patients with Pompe disease: Data from the Pompe Registry by Arnold J. J. Reuser et al., https://doi.org/10.1002/humu.23878 and Extension of the Pompe mutation database by linking disease‐associated variants to clinical severity by Monica Y. Niño et al., https://doi.org/10.1002/humu.23854 . Cover image © Dr Pim Pijnappel and Dr AJJ Reuser Images.